Absolute polar duty cycle division multiplexing for optical communication - Abas @ Ismail, Ahmad Fauzi (2009)
The present invention relates to an absolute polar duty cycle division multiplexer for optical communication (hereinafter also referred as AP-DCDM) at high aggregate bit rate is presented. The results show its clear advantage of over conventional RZ-OOK in terms of spectral width and dispersion tolerance. Using this electrical multiplexing/demultiplexing technique, more than two users can be carried over the same WDM channel. Consequently, the capacity utilization of the WDM channels can be increased tremendously at tolerable penalty. The increment of amplitude level in reference to the number of user is reduced by using absolute polar signaling. AP-DCDM has better receiver sensivity and CD tolerance as compared to conventional NRZ-OOK and RZ-DQPSK.